Rutaecarpine alleviates hepatic ischemia‒reperfusion injury in liver transplantation by inhibiting inflammatory response and oxidative stress - Liu, Yan; Qi, Feng; Xiang, Lun-Jian; Yi, Zhu-Jun; Li, Sheng-Wei (Frontiers in Pharmacology, 2025)
BackgroundDonation after circulatory death (DCD) livers are limited by mandatory warm ischemia and are more susceptible to ischemia‒reperfusion injury (IRI). Inflammation and oxidative stress play key roles in the development of hepatic IRI, and Rutaecarpine (Rut) has anti-inflammatory and anti-oxidative stress effects. The aim of this study was to investigate whether Rut can alleviate hepatic IRI in liver transplantation (LT) and to explore the underlying mechanisms.MethodsRat DCD LT and oxygen-glucose deprivation/reoxygenation (OGD/R) cell models were established to clarify the effect of Rut on hepatic IRI. The key molecules involved in the hepatoprotective effects of Rut were identified through joint analysis of data from LT patients and drug targets. The target was further validated by in silico, in vivo and in vitro experiments.ResultsRut significantly alleviated liver dysfunction, pathological injury, and apoptosis and improved the survival rate of the rats subjected to LT. In addition, Rut significantly inhibited inflammatory response and oxidative stress. Rut also had similar effects on OGD/R-induced hepatocyte injury. Mechanistically, bioinformatics analysis and in vivo and in vitro experiments revealed that PDE4B may be a key target by which Rut exerts its protective effect, and molecular docking and cellular thermal shift assay confirmed this result. The function of PDE4B was studied via gene intervention technology, and the results showed that PDE4B can aggravate hepatic IRI. Furthermore, PDE4B overexpression abrogated the protective effect of Rut on the liver in LT.ConclusionRut alleviates hepatic IRI by targeting PDE4B to inhibit inflammation and oxidative stress. These findings highlight the potential of Rut as a drug candidate for the treatment of patients undergoing LT.